The Courage to Care: Teacher Compassion Predicts More Positive Attitudes Toward Trauma-Informed Practice - Dobutowitsch, Mira (Springer Nature, 2022)
Purpose: With greater awareness of the prevalence and impact of childhood trauma and adversity, teachers are now assuming a more active role in creating emotionally healthy environments and responding to student distress. However, supporting trauma-affected students can be a source of amplified teacher stress. Compassion has been identified as a promising construct for frontline professionals in terms of promoting psychological wellbeing, and increasing the sensitivity to detect, tolerate and respond to distress in others. It has also been identified as an important aspect of trauma-informed practice. Nevertheless, the role of compassion in teachers’ attitudes towards, and readiness for implementing trauma-informed practices has not yet been explored. This study aimed to address this gap. Methods. A sample of 377 primary and post-primary teachers in Ireland completed the Attitudes Related to Trauma-Informed Care Scale, the Professional Quality of Life Scale, the Self-Compassion Scale, and a socio-demographic survey. Results. Teachers were found to hold generally positive attitudes toward trauma-informed care. They exhibited low to moderate levels of secondary traumatic stress and burnout, and notably high levels of compassion satisfaction, indicating that they tend to embrace their caring role and find meaning and purpose in their work. Regression analyses showed that compassion satisfaction was the strongest predictor of positive attitudes toward trauma-informed care, followed by self-compassion. Older teachers were more likely to display positive attitudes toward trauma-informed care, whilst teachers in single-sex boys’ schools held attitudes that were less favorable. Conclusion. This study suggests potential benefits for both teachers and students of positioning compassion at the center of educational policy and practice. The results are contextualized within the Irish and international educational landscape.
Keywords: Teacher wellbeing; Stress and burnout; Ireland; Compassion; Trauma-informed practice; Childhood trauma; Wellbeing; Survey; Education policy; Primary school; Post-primary; Research Subject Categories::SOCIAL SCIENCES; Education